Exploring attitudes to NATO in Republika Srpska. Issue 4 (2nd October 2015) - Roberts,; Halilović,; Becirević,; Hewer,
Abstract : The role of NATO in the maintenance of regional security was assessed from a random sample of 1000 residents in the Serbian entity Republika Srpska (RS) – part of Bosnia and Herzegovina – in the fall of 2011. Attitudes to NATO were largely divided along ethnic lines. Evidence of positive attitudes towards NATO was mostly found among (i) non-Serbs (71%) compared with Serbs (18%), (ii) women and (iii) respondents over 65 years. Specific features underpinning these responses were analysed and modelled, which included consequences of NATO membership in the domain of security, economics, international reputation and international relations. A main effects general linear model was able to predict 25.7% of the variance. Ethnicity, age group, level of education, degree of trust in politicians, understanding the role and purpose of NATO and the importance attached to reaching a common understanding of the past were significant predictors. Logistic regression models of a pro- or anti-NATO stance predicted considerably higher variation and showed that the importance attached to reaching a common understanding of the past is predicated, not on ethnicity per se, but on general responses to NATO and whether Serbia would benefit from NATO membership. The implications of these findings for political stability and reconciliation within the region are discussed.